PHENOLOGY AND LIFE CYCLES OF SOME COCCINELLID SPECIES - Buriyeva , X.P.; Arabova , N.Z; Yoqubov S, Yoqubov S; Sattorova M.A, Sattorova M.A (Actual problems and prospects of the study of the fauna, 2024)
This article explores the phenology of certain species within the Coccinellidae family, focusing on aspects such as dormancy, active life stages, generational frequency, and overwintering phases of beetles, all of which are closely associated with climatic factors and geographic distribution.